Role of NPK Fertilizer and Planting Ates on the Vegetative and Flowering Growth Tributes of Two Varieties of Snake Melon - Al-Sharabi, Khaled Mustafa Ali; Al-Jubouri, Amer Abdullah Hussein (Journal La Lifesci, 2024)
The purpose of this research was to determine the response of two varieties of snake melon to the levels of NPK fertilizer and planting dates in terms of vegetative and flowering growth characters. The experiment was conducted in the vegetable field of the Department of Horticulture and Landscape Engineering/College of Agriculture and Forestry University of Mosul during the spring season 2023. The study included three factors. The first factor: Two local cucumber varieties: (gennxt and Mosli). The second factor was compound fertilizer (NPK) at four levels (270, 180, 90.0 kg/ha!) and the third factor: planting dates. Two planting dates were chosen: (4/1/2023) and (4/20/2023). Compound fertilizer (NPK) was added to the soil in three stages, the first three weeks after planting and after the plants reached the appropriate size (four true leaves), and the second and third at an interval of 20 days between one stage and the next. Thus, the experiment included 18 treatments (2 x 2 x 4 = 16). With three replications, the experiment was carried out in the field using a factorial experiment according to a randomized complete block design (RCBD), where the treatments were randomly distributed according to the design used in the experiment. The results were analyzed statistically according to the design used, and the means were compared according to Duncan's multinomial test at the probability level of 0.05.